Contribution of dissolved organic carbon to total alkalinity in Enhanced Weathering experiments - Lukas Rieder; Mathilde Hagens; Reinaldy Poetra; Alix Vidal; Tullia Calogiuri; Anna Neubeck; Abhijeet Singh; Thomas Corbett; Harun Niron; Sara Vicca; Siegfried E. Vlaeminck; Iris Janssens; et al. (Applied Geochemistry, 2026)

A density-based method to objectively quantify earthworm activity - Péter Garamszegi; Tullia Calogiuri; Mathilde Hagens; Alix Vidal; Jan Willem Van Groenigen (Applied Soil Ecology, 2025)

How earthworms thrive and drive silicate rock weathering in an artificial organo-mineral system - Tullia Calogiuri; Iris Janssens; Alix Vidal; Jan Willem Van Groenigen; Tim Verdonck; Thomas Corbett; Jens Hartmann; Anna Neubeck; Harun Niron; Reinaldy P. Poetra; Lukas Rieder; Thomas Servotte; et al. (Applied Geochemistry, 2025)

Is the climate change mitigation effect of enhanced silicate weathering governed by biological processes? - Sara Vicca; Daniel S. Goll; Mathilde Hagens; Jens Hartmann; Ivan A. Janssens; Anna Neubeck; Josep Peñuelas; Sílvia Poblador; Jet Rijnders; Jordi Sardans; Eric Struyf; Philipp Swoboda; et al. (Global Change Biology, 2022)
A number of negative emission technologies (NETs) have been proposed to actively remove CO 2 from the atmosphere, with enhanced silicate weathering (ESW) as a relatively new NET with considerable climate change mitigation potential. Models calibrated to ESW rates in lab experiments estimate the global potential for inorganic carbon sequestration by ESW at about 0.5–5 Gt CO 2 year −1 , suggesting ESW could be an important component of the future NETs mix. In real soils, however, weathering rates may differ strongly from lab conditions. Research on natural weathering has shown that biota such as plants, microbes, and macro‐invertebrates can strongly affect weathering rates, but biotic effects were excluded from most ESW lab assessments. Moreover, ESW may alter soil organic carbon sequestration and greenhouse gas emissions by influencing physicochemical and biological processes, which holds the potential to perpetuate even larger negative emissions. Here, we argue that it is likely that the climate change mitigation effect of ESW will be governed by biological processes, emphasizing the need to put these processes on the agenda of this emerging research field.

Current estimates of K 1 * and K 2 * appear inconsistent with measured CO 2 system parameters in cold oceanic regions - Olivier Sulpis; Siv K. Lauvset; Mathilde Hagens (Ocean Science, 2020)
Seawater absorption of anthropogenic atmospheric carbon dioxide (CO2) has led to a range of changes in carbonate chemistry, collectively referred to as ocean acidification. Stoichiometric dissociation constants used to convert measured carbonate system variables (pH, pCO2, dissolved inorganic carbon, total alkalinity) into globally comparable parameters are crucial for accurately quantifying these changes. The temperature and salinity coefficients of these constants have generally been experimentally derived under controlled laboratory conditions. Here, we use field measurements of carbonate system variables taken from the Global Ocean Data Analysis Project version 2 and the Surface Ocean CO2 Atlas data products to evaluate the temperature dependence of the carbonic acid stoichiometric dissociation constants. By applying a novel iterative procedure to a large dataset of 948 surface-water, quality-controlled samples where four carbonate system variables were independently measured, we show that the set of equations published by Lueker et al. (2000), currently preferred by the ocean acidification community, overestimates the stoichiometric dissociation constants at temperatures below about 8 ∘C. We apply these newly derived temperature coefficients to high-latitude Argo float and cruise data to quantify the effects on surface-water pCO2 and calcite saturation states. These findings highlight the critical implications of uncertainty in stoichiometric dissociation constants for future projections of ocean acidification in polar regions and the need to improve knowledge of what causes the CO2 system inconsistencies in cold waters.

Phosphorus Cycling and Burial in Sediments of a Seasonally Hypoxic Marine Basin - Fatimah Sulu-Gambari; Mathilde Hagens; Thilo Behrends; Dorina Seitaj; Filip J. R. Meysman; Jack Middelburg; Caroline P. Slomp (Estuaries and Coasts, 2018)